Development of zinc oxide - inverse opals for photocatalysis applications - Lim, Han Wee (Nanyang Technological University, 2024)
With increasing scrutiny on the world around us and the effects the environment has on us, it is important for us to have an effective method to remediate the affected environment. Photocatalytic treatment proves to be a straightforward and economical method, specifically with the use of heterogenous photocatalyst. In this study, Zinc oxide was studied over the more well-known Titanium oxide, due to cheaper cost and faster reaction rate. To improve the photo efficiency of Zinc oxide, Zinc oxide – Inverse opals (ZnO–IO) were fabricated in order to shift the absorption peak of ZnO into the Visible light region as well as increase the surface area in contact during the photocatalytic treatment. The fabricated nanostructure would then be analysed using SEM and XRD to ensure that the correct morphology and compound has been fabricated. After which, UV-Vis analysis was conducted to determine the absorption peak of the fabricated nanostructures. It was concluded that under the same electrodeposition conditions, that Zinc Nitrate precursor was more suited to fabricate Inverse opals (IO) structure. Although, the absorption peak of both fabricated nanostructures did not fall under the Visible light region, there were still a slight red shift in absorption peak as well as increased absorption in the Visible light region using the Zinc Nitrate precursor. There was also a small absorption peak observed for the nanostructure fabricated using Zinc Acetate precursor at 428 nm. To achieve better photo efficiency, other works such as doping can be done.